If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11x-1+x-9=-12(5-2x)+2(-x-5)
We simplify the equation to the form, which is simple to understand
11x-1+x-9=-12(5-2x)+2(-x-5)
Reorder the terms in parentheses
11x-1+x-9=+(-60+24x)+2*(-x-5)
Remove unnecessary parentheses
+11x-1+x-9=-60+24x+2+*(-x-5+)
Reorder the terms in parentheses
11x-1+x-9=-60+24x+(-2x-10)
Remove unnecessary parentheses
+11x-1+x-9=-60+24x-2x-10
We move all terms containing x to the left and all other terms to the right.
+11x+1x-24x+2x=-60-10+1+9
We simplify left and right side of the equation.
-10x=-60
We divide both sides of the equation by -10 to get x.
x=6
| (-5xy-11)(5xy+11)= | | -4=8n+6-3n | | 6-4x=7x-9+8 | | 32=6 | | (-5xy-11)(-5xy+11)= | | x+(-4)=1 | | 90= | | 18-(3b-15)=6(2b+5) | | 7n-17=4n+7 | | (-19)+x=-21 | | 4-2(3-2w)=3(w+1)-10 | | 2(x+3)-3(2x+4)=8-6x | | 2=-x+x+2 | | (5y+7)-(5+4y)=12 | | 11=7a-7+2a | | 720=8b-560 | | 7x+8=5x+6 | | 7.8=x+5.8 | | x^2+x=27 | | 5v-v=8 | | 0.32(1600)=0.3(1600)+32 | | x^2+18x+83=0 | | 9.75=x-8.35 | | 1.5x+2=1x+2.5 | | 7=2x-2x | | 14x^2+13x+3=0 | | 5m=43 | | 2.25+x=7.25 | | -7+9x=-43 | | -6+7(-2)=8 | | 1.5x-2=x-2.5 | | 10(6-5V)+7=47 |